KEMITRAAN PENGELOLAAN SAMPAH PLASTIK DI TPA TEMUREJO KABUPATEN BLORA - Milasari, Rini; Sunu Astuti, Retno; Kismartini, Kismartini (Journal of Public Policy and Management Review, 2024)
Temurejo landfill in Blora Regency conducts waste management through a partnership with BSI Berkah Mustika Poring. Waste management has been implemented well so that not all waste is put into the landfill zone. Blora district won the Adipura award 5 times in the cleanest small city category. The achievement of waste management performance shows good results with almost 100% managed waste, namely 99.97%. The purpose of the study was to analyze the partnership of plastic waste management in Temurejo landfill and analyze the success factors and inhibiting factors of the partnership. This research uses a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The research data comes from primary data obtained through interviews while secondary data is obtained through journals and the internet. The results showed that the intertwined partnership model was a collaborative Linear partnership model of partners because there was no legality proving that in the intertwined partnership the status of legality was not too considered so that the collaborative Linear partnership model of partners was appropriate. The established partnership also has a complementary vision and mission. Success factors show 3 indicators that have been met, namely input, process, and output, while the outcome indicator is still less than optimal. Factors inhibiting the partnership, namely 1) Ignorance of some members involved in the partnership regarding the legality of the partnership, 2) The absence of written legality status as evidence of the partnership implementation agreement, 3) Lack of funds for partnership operational needs. Suggestions offered, namely 1) It is necessary to make a legality document in the form of an MoU to clarify the status of the partnership. 2) Expanding the sales market for plastic seed products. 3) Looking for investors to help fund the waste management partnership operations.